The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.31616/asj.2022.0184
|View full text |Cite
|
Sign up to set email alerts
|

Laminoplasty versus Laminectomy in the Treatment of Primary Spinal Cord Tumors in Adult Patients: A Systematic Review and Meta-analysis of Observational Studies

Abstract: The present systematic review and meta-analysis was conducted to compare the safety and efficacy of the two approaches for primary spinal cord tumors (PSCTs) in adult patients (laminoplasty [LP] vs. laminectomy [LE]). LE is one of the most common procedures for PSCTs. Despite advantages of LP, it is not yet widely used in the neurosurgical community worldwide. The efficacy of LP vs. LE remains controversial. Adult patients over 18 years of age with PSCT at the level of the cervical, thoracic, and lumbar spine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
2
2
Order By: Relevance
“…Laminoplasty, posterior laminectomy and fusion, or ACDF combined with posterior decompression might result in better outcomes in these clinical scenarios. 1,12,15,30,31 However, although the present study demonstrated poor clinical outcomes for ACDF in the setting of severe CCLF, it could not prove the superiority of the posterior or combined approach over ACDF for cervical myelopathy aggravated by CCLF. Further studies should focus on this comparison in the future.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Laminoplasty, posterior laminectomy and fusion, or ACDF combined with posterior decompression might result in better outcomes in these clinical scenarios. 1,12,15,30,31 However, although the present study demonstrated poor clinical outcomes for ACDF in the setting of severe CCLF, it could not prove the superiority of the posterior or combined approach over ACDF for cervical myelopathy aggravated by CCLF. Further studies should focus on this comparison in the future.…”
Section: Discussioncontrasting
confidence: 82%
“…As ACDF for CCLF is associated with poor clinical results, performing posterior surgery or using a combined approach could be considered when grade 2 posterior cord compression by ligamentum flavum is identified on preoperative MRI imaging. Laminoplasty, posterior laminectomy and fusion, or ACDF combined with posterior decompression might result in better outcomes in these clinical scenarios 1,12,15,30,31 . However, although the present study demonstrated poor clinical outcomes for ACDF in the setting of severe CCLF, it could not prove the superiority of the posterior or combined approach over ACDF for cervical myelopathy aggravated by CCLF.…”
Section: Discussioncontrasting
confidence: 68%
“…Factors potentially leading to instability after laminoplasties are preoperative deformities and performing facetectomies. None of these criteria were present in our cohort [19][20][21].…”
Section: Discussionmentioning
confidence: 93%
“…The vast majority of patients underwent laminectomy rather than laminoplasty, however, the rationale for this decision was generally not provided. Especially in junctional regions of the spine and in multi-level approaches, we prefer restoring the anatomy by laminoplasty - an approach that appears to be supported by recent literature ( Sun et al, 2019 ; Byvaltsev et al, 2023 ). In one of our cases, we also chose laminoplasty over laminectomy in order to reduce the risk of post-laminectomy kyphosis and to potentially facilitate the approach in case of a potential future revision surgery.…”
Section: Discussionmentioning
confidence: 94%